Peranan Pemerintah Desa dalam Menangani Konflik Peternakan Ayam Broiler di Desa Pucanglaban Kabupaten Tulungagung - Laily Purnawati (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2020)
Starting in 2010, the trend of broiler chicken farming has increased significantly. The increasing demand for chicken farms produces changes or shifts the source of income from agriculture to livestock. At the beginning of the establishment of the stables, public acceptance was very open but when the scale of the farm became large there were several complaints because of the smell and flies. The lack of caring attitude of broiler breeders makes the community a little angry and this is what causes differences of opinion between them. This research goal was conducted to determine the handling of conflicts between chicken breeders and the surrounding community by the Pucanglaban village government. To find out the strategy of the village government in dealing with conflicts between broiler breeders and the community, researchers used a qualitative descriptive research method with snowball sampling models. Based on the research results, it can be seen that in order to resolve the conflict, the village government acts as a facilitator, mediator, and regulator so that an agreement can be reached by minimizing losses between the two parties. In the future, it is hoped that there will be standard rules made especially by the village government regarding the procedures and procedures for establishing a farm cage so that it can avoid potential conflicts between chicken breeders and the community.